Tradition and Spirituality: Exploring the Motifs of Rifaiyah Batik in the Context of Islamic Values - Choirunnisa Rezky Ramadhani; Fajar Ciptandi (IBDA` : Jurnal Kajian Islam dan Budaya, 2025)
Batik Rifaiyah is a cultural heritage of the Rifaiyah Community located in Kalipucang Wetan Village, Batang Regency, Central Java. It serves as an expression of Islamic spirituality. This type of Batik represents artistic craftsmanship and is a medium for teaching Islamic values through symbols and motifs. However, understanding the philosophical values and foundational aspects of Rifaiyah Batik is currently limited to the oral traditions passed down by batik makers and the Rifaiyah Community, with insufficient written documentation. This study aims to explore and comprehend the fundamental principles of Rifaiyah Batik as a manifestation of Islamic spiritual art, focusing on the Pelo Ati and Materos Satrio motifs. The research employs a qualitative method utilizing a social phenomenology approach. It includes observations of the batik motifs, in-depth interviews with batik makers, and a review of relevant literature. The analysis is guided by the Pyramid Base Guiding Craft Innovation theory, which identifies four crucial dimensions in the batik tradition: Traditional Artifacts, Traditional Ecology, Teaching of Tradition, and Non-Material Culture. The findings reveal that Rifaiyah Batik reflects Islamic values through theological, aesthetic, and artistic ethics. Theologically, it avoids depicting living beings, using arabesque to express Tawheed. Aesthetically, its colors are inspired by the Qur'an. Artistically, its meticulous craftmanship is an act of worship.